Transitory Fetal Skin Edema in a Pregnant Patient with a Mild SARS-CoV-2 Infection - Alicia Martínez-Varea; Julia Desco-Blay; Sagrario Monfort; María Hueso-Villanueva; Alfredo Perales-Marín; Vicente José Diago-Almela (Case Reports in Obstetrics and Gynecology)
Background. Vertical transmission of the Coronavirus Disease 2019 (COVID-19) is still controversial. Additionally, the consequences of the infection during pregnancy in the offspring also are unknown. Case. A transitory fetal skin edema and polyhydramnios have been demonstrated by ultrasound in a pregnant patient with COVID-19 after a negative RT-PCR for SARS-CoV-2. The fetal findings presented a spontaneous resolution in utero, and abnormal findings were not found in the newborn. Conclusion. Women who have undergone SARS-CoV-2 infection during pregnancy should receive a subsequent appropriate follow-up in order to clarify the fetal consequences of the novel coronavirus, if any.